Bichir external gills arise via heterochronic shift that accelerates hyoid arch development - Stundl, Jan; Pospisilova, Anna; Jandzik, David; Fabian, Peter; Dobiasova, Barbora; Minarik, Martin; Metscher, Brian D; Soukup, Vladimir; Cerny, Robert (eLife, 2019)
In most vertebrates, pharyngeal arches form in a stereotypic anterior-to-posterior progression. To gain insight into the mechanisms underlying evolutionary changes in pharyngeal arch development, here we investigate embryos and larvae of bichirs. Bichirs represent the earliest diverged living group of ray-finned fishes, and possess intriguing traits otherwise typical for lobe-finned fishes such as ventral paired lungs and larval external gills. In bichir embryos, we find that the anteroposterior way of formation of cranial segments is modified by the unique acceleration of the entire hyoid arch segment, with earlier and orchestrated development of the endodermal, mesodermal, and neural crest tissues. This major heterochronic shift in the anteroposterior developmental sequence enables early appearance of the external gills that represent key breathing organs of bichir free-living embryos and early larvae. Bichirs thus stay as unique models for understanding developmental mechanisms facilitating increased breathing capacity.
Keywords: bichir; pharynx; head; breathing; external gills